사과/배 부산물 및 표고버섯균사체를 이용한 발효물 개발 - 김진경(Jin-Kyeong Kim); 조승화(Seong-Wha Jo); 김은지(Eun-Ji Kim); 정도연(Do-Youn Jeong) (Han'guk Sikp'um Kwahakhoe Chi = Korean Journal of Food Science and Technology, 2019)
The purpose of this study was to investigate the possibility of enhancing the functional compounds in apple and pear pomace (APP) by fermentation with mycelia from the mushroom Lentinula edodes. A 30% (w/v) APP with added rice bran and Biji was fermented with L. edodes at 24o C and 80% humidity. The cellulase and pectinase activities in the fermented APP (FAPP) were higher than those in the non-fermented control. In addition, the physiological activities of the FAPP, including DPPH, ABTS radical scavenging, and SOD-like activity, as well as the total polyphenol and βglucan contents were higher than those in the control. FAPP treatment significantly reduced LPS-induced nitric oxide (NO) levels in Raw 264.7 cell. Therefore, FAPP treatment was considered to more effectively suppress cell injury caused by inflammatory cytokines through inhibition of LPS-induced NO production. These results suggest that the levels of functional components in APP can be increased by fermentation with this mushroom mycelium. However, further studies are needed before it can be used as a functional material.